(untitled) (Interdisciplinary Studies Journal, 2025)
The judicialization of health in Brazil has been a key mechanism to ensure access to treatments and medicines, especially for people with Autism Spectrum Disorder (ASD). This article analyzes the challenges, impacts, and perspectives of this phenomenon, based on a bibliographic and documentary review. It discusses the legal framework supporting the right to health, the causes of judicialization such as the insufficiency of the Unified Health System (SUS) and the complexity of treatments, the jurisprudential criteria adopted by higher courts, and the impacts on equity and sustainability of the health system. It concludes that, although the judicial route is essential to ensure individual rights, the implementation of more efficient and inclusive public policies is urgently needed to reduce dependence on the Judiciary.